The Synergistic Effects of Animated Media and KWL Strategy on EFL Students’ Reading Skills - Nur Azizah Marinda; Hanomi Hanomi; Yufni Faisol (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
The main problem in learning maharah qirā’ah (Arabic reading skills) at MTsS Al Makmur lies in students’ low interest and limited comprehension of Arabic texts. This issue stems from the use of monotonous teaching strategies and instructional media that fail to stimulate active engagement or meaningful learning. To address this problem, an innovative combination of animated videos and the Know–Want to Know–Learned (KWL) strategy was introduced to enhance students’ reading comprehension and motivation. This study aimed to investigate the effect of integrating animated videos with the KWL strategy in maharah qirā’ah instruction among seventh-grade students at MTsS Al Makmur. The research employed a quasi-experimental design using a non-equivalent control group, involving one experimental and one control class. Data were analyzed using a t-test to measure the difference in students’ reading achievement. The results revealed a t-value of 4.874 with a significance level of 0.001, which is lower than 0.05, indicating a statistically significant improvement in students’ reading skills. The study concludes that combining animated videos with the KWL strategy effectively enhances students’ engagement, comprehension, and learning outcomes. This finding contributes to Arabic language pedagogy by demonstrating how digital media and metacognitive strategies can be integrated to foster more effective maharah qirā’ah instruction.